Organizational Citizenship Behavior among Teachers: The Role of Organizational Pride and Organizational Justice - Fadhilah, Fathin; Izzati, Umi Anugerah; Mulyana, Olievia Prabandini; Isa, Khairunesa (Program Studi Psikologi UIN Sunan Ampel Surabaya, 2026)
T Organizational Citizenship Behavior (OCB) is a crucial factor in the success of organizations, particularly educational institutions. This study aims to determine the role of organizational pride and organizational justice on organizational citizenship behavior among teachers. The present study used a quantitative research method with a correlational design. Participants of this study were teachers at the